Low-cost portable system for measuring thermal conductivity of building - Tunti Alanocca, Jaime Alberto (2024)
The developed system allows to measure the thermal conductivity of solid materials used as thermal insulators in building bioclimatic houses on high Andean zones. A unidirectional heat flow model through a sample of dimensions 4.0 cm x 4.2 cm x 1.35 cm has been considered. K-type thermocouples were used to measure the temperature's gradient. The obtained values were: 0.97 Wm−1°C−1 for glass, 0.38 Wm−1°C−1 in the ignimbrite, 0.58 Wm−1°C−1 for the roof brick and 0.34 Wm−1°C−1 in the adobe with Stipa ichu. These materials have been evaluated considering their abundance and use in house building on the Arequipa department high zones.